18F-FDG PET-CT in the Management of Patients Receiving Definitive Radiotherapy for Malignancies of the Head and Neck. (31st March 2015) - Franc, Benjamin L.; DeLemos, Christi; Jones, Christopher
Abstract : The study investigated the utility and timing of 18 F-FDG PET-CT to evaluate for residual/recurrent or metastatic HNC in patients treated with definitive intensity modulated radiation therapy (IMRT) with or without chemotherapy, planned with 18 F-FDG PET-CT. The incidence and timing of locoregional recurrence, distant metastatic disease, new primary malignancies, and death were evaluated in 261 patients retrospectively. Findings were classified based on pathology or clinical follow-up and the sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of FDG PET-CT were determined overall as well as at the time of each 18 F-FDG PET-CT. The overall accuracy for 18 F-FDG PET in the detection of residual/recurrent malignancy or metastatic disease was 96.4%. Of those in whom cancer recurred locally, 57% were identified based on physical examination and other imaging findings and 43% were identified initially on 18 F-FDG PET-CT surveillance imaging when no disease was evident clinically. 18 F-FDG PET-CT has a high diagnostic capability of detecting residual/recurrent malignancy or malignant metastatic disease in patients with HNC following IMRT ± concurrent chemotherapy, supporting 18 F- FDG PET-CT's use to evaluate patients for recurrent malignancy in the post-IMRT period, even without clinical evidence of disease.